Effects of perinatal exposure to lead (Pb) on purine receptor expression in the brain and gliosis in rats tolerant to morphine analgesia. (2nd January 2016) - Baranowska-Bosiacka, Irena; Listos, Joanna; Gutowska, Izabela; Machoy-Mokrzyńska, Anna; Kolasa-Wołosiuk, Agnieszka; Tarnowski, Maciej; Puchałowicz, Kamila; Prokopowicz, Adam; Talarek, Sylwia; Listos, Piotr; Wąsik, Agnieszka; Chlubek, Dariusz
Abstract: The aim of the present study was to investigate the molecular effects of perinatal exposure to lead (Pb) on protein and mRNA expression of purine receptors: P2X4, P2X7, adenosine receptor A1; and astrocytes (GFAP mRNA expression) and on microglia activation (Iba1 mRNA expression) in several structures of the mesolimbic system (striatum, hippocampus, prefrontal cortex) in rats expressing tolerance to the antinociceptive effect of morphine. Rat mothers were orally treated with 0.1% lead acetate from conception, through gestation, and postnatally, as well as to offspring up to day (PND) 28; subsequently molecular studies were conducted on adult (PND 60) male rats. Morphine tolerance developed more strongly in rats perinatally exposed to Pb. The analysis revealed a significant up-regulation of protein and mRNA P2X4 receptor expression in the striatum and prefrontal cortex but not in the hippocampus; P2X7 protein and mRNA receptor expression in the striatum and hippocampus, but not in the prefrontal cortex; A1 protein receptor expression in all investigated structures and A1 mRNA expression in the striatum and hippocampus; Iba1 mRNA expression in the striatum and hippocampus; and GFAP mRNA expression in the striatum and prefrontal cortex. Immunohistochemical analysis has also revealed significant alterations. Strong expressions of P2X4, P2X7, A1 receptors, astrocytes and microglia activation were observed in the hippocampus in Pb and/or morphine treated rats. The higher expression of purine receptors and glial cell activation are important markers of neuroinflammatory processes. Therefore, we conclude that Pb-induced neuroinflammation may be responsible for the intensification of morphine tolerance in the Pb-treated rats. Additionally, the dysregulation of A1 adenosine receptors, mainly in the hippocampus, may also be involved in the intensification of morphine tolerance in Pb-treated rats. Our study demonstrates the significant participation of environmental factors in addictive process; additionally, it shows the necessity of modification of addictive disorder with neuroprotective agents.